0
$\begingroup$

I have the following problem:

Let $\phi:G\to H$ be an isomorphism of groups, and let $N$ be a normal subgroup of $G$. Then $\phi(N)$ is a normal subgroup of $H$. Prove that $\phi$ induces an isomorphism such that $G/N\simeq H/\phi(N)$.

How would one go about this problem? Is the first isomorphism theorem handy here? Thanks for any help!

$\endgroup$
3
  • $\begingroup$ You can see that $\phi$ induces a homomorphism $G\to H/\phi(N)$. Then you can find its kernel and use the isomorphism theorem $\endgroup$ – Maxime Ramzi Feb 19 '17 at 8:34
  • $\begingroup$ How exactly would $\phi$ induce a homomorphism on $G\to H/\phi(N)$? $\endgroup$ – Sir_Math_Cat Feb 19 '17 at 8:35
  • 1
    $\begingroup$ It's the composition of $\phi$ with the canonical homomorphism $H \to H/\phi(N)$. $\endgroup$ – Derek Holt Feb 19 '17 at 8:50
3
$\begingroup$

Let us solve the problem in a more general setting:

if $\phi :G \to H$ is a surjective group morphism and $N \unlhd G$, and if $\ker \phi \subseteq N$, then $G/N \simeq H/\phi(N)$.

The hypothesis $\ker \phi \subseteq N$ is essential. Without it, the statement is no longer true in general, as is shown by the example $N = \{e\}$: you would get $G \simeq H$, which is not necessarily true. Another counterexample is given by $\phi(g) = e \ \forall g \in G$ and $N \ne G$ arbitrary: in this case, the conclusion of the problem would be $G/N \simeq H$ which again is not true in general, because the left-hand side depends on the arbitrary $N$ while the right-hand side does not.

Surjectivity is essential in order to have $\phi(N) \unlhd H$ (without surjectivity, you only have $\phi(N) \le H$ in general, even though $N \unlhd G$).

The solution is standard algebraic manipulation, and your intuition is correct, the first isomorphism theorem will do the job. In order to apply it, we'll have to construct a group morphism $f : G \to H/\phi (N)$ having $\ker f = N$. Since we don't have too many ingredients in our problem, we don't really have a choice: if $p : H \to H/\phi (N)$ is the natural projection $h \mapsto p(h) = \hat h$, then define $f = p \circ \phi$. Being a composition of morphisms, it itself will be a morphism.

To find $\ker f$, consider the sequence of equivalences

$$g \in \ker f \iff f(g) = \hat e \iff p(\phi (g)) = \hat e \iff \phi (g) \in \phi (N) \iff \exists n \in N \text{ such that } \\ \phi(g) = \phi(n) \iff \phi(gn^{-1}) = e \iff gn^{-1} \in \ker \phi \subseteq N \iff g \in Nn \subseteq N \iff g \in N$$

which shows that $\ker f = N$, and now the first isomorphism theorem immediately gives you $G/N \simeq H/\phi(N)$.

$\endgroup$
0

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.